Examining the Asian American leadership gap and inclusion issues with federal employee data: Recommendations for inclusive workforce analytic practices - Goon, Caroline; Bruce, Tamara A.; Lun, Janetta; Lai, Gabriel Y.; Chu, Serena; Le, Phuong-Tu (Frontiers in Research Metrics and Analytics, 2022)
In April 2021, a coalition of employee resource groups called the Federation of Asian American, Native Hawaiian, and Pacific Islander Network, or FAN, was established at the National Institutes of Health (NIH). The coalition aims to be a unifying voice that represents and serves these diverse communities. Discussion within the group centered around the persistent inequities and the lack of inclusion that the Asian American communities have long endured. Two common themes emerged from these discussions: (1) a leadership gap for Asian Americans in senior leadership and managerial positions, and (2) the everyday experience of exclusion. Asian Americans represent nearly 20% of the NIH permanent workforce yet make up only 6% of the senior leadership positions. These two issues reflect the sentiment that Asian Americans often feel invisible or forgotten in the discourse of structural racism and organizational inequities, especially in organizations in which they are numerically overrepresented. The purpose of this manuscript is to raise awareness of Asian American concerns in the federal workforce and how current employment and workforce analytic practices in this domain might contribute to the invisibility. To accomplish this goal, we will (1) describe relevant historical and contemporary contexts of Asian American experience undergirding their inclusion and visibility concerns; (2) present data analyses from available data sources to provide a deeper understanding of the Asian American leadership gap and lack of inclusion concerns; (3) highlight data availability and analytic challenges that hinder the ability to address the inequity and invisibility issues; and (4) recommend practices in data collection, measurement, and analysis to increase the visibility of this community in the federal workforce.